Effects of Dual Tasks Training on Balance Performance and Cognitive Functions in Older Adults with Mild Cognitive Impairments: A Randomized Controlled Study - Rungseethanakul, Somchanok; Yingyongyudha, Anyamanee (Journal of Food Health and Bioenvironmental Science, 2023)
Mild cognitive impairment (MCI) is a condition of older adult who are at the transitional state between the cognitive changes of normal aging and very early dementia. Numerous studies have established that mild exercise or cognitive training has positive effects on physical and cognitive functions in healthy older adults. Newly, the possibility of combined of physical exercise and cognitive training get noticed in the older adults with MCI. The objective of this study is to investigate the effect of mild exercise with cognitive training in older adults with MCI on measures of balance performance and cognitive functions. Ninety older adults with MCI were randomized into three groups. Mild exercise (ME) group (n = 30) underwent chair-based exercise, cognitive training (CT) group (n = 30) received Stroop color and word task training, while the mild exercise with cognitive training (ME+CT) group (n = 30) received both of them in the same time. In terms of demographic characteristics, there was no significant differences among three groups in baseline data. All groups underwent the training for 45 minutes per sessions, 12 training sessions within 30 days. Participants were evaluated for balance performance (via Mini-Balance Evaluation Systems Test (Mini-BESTest)) and cognitive functions (via Mini-Mental State Examination (MMSE)) prior to the training and then we immediately re-assessed after training. Significant main effects of group in Mini-BESTest (p=0.003) and MMSE (p = 0.037), and main effect of time in Mini-BESTest (p = 0.033) and MMSE (p = 0.012) (ME+CT > CT > ME group) were found. The ME+CT group also demonstrated improved balance performance and cognitive functions compared to the ME or CT group (posttraining > baseline). A combination of mild exercise and cognitive training can improve balance ability and cognitive functions in older adults with MCI as well as mild exercise or cognitive training. It might be beneficial effect for delaying the declining functional capacity in older adults with MCI.